How does the inclusion of children with disabilities in schools impact some of the interveners of the educational community? - D' Oliveira, Maria Madalena Gonçalves Tenda Corrêa (2020)
This project seeks to study the impact of including disabled students through the perspective of schools directors and teachers. Following an inductive approach, a data structured was developed based on the insights of 30 interviewees. It was concluded that disabled students positively impact both interveners, contributing to a professional growth and human enrichment. Also, these ideas share a common background, as both reinforce the importance of school leaders, who create environments appropriate for increased motivation. In turn, schools revealing virtuous practices lead their communities to become more open to change and, consequently, more inclusive.